Occupations and Gender in Turkish Children's Literature - Turhan, Osman; Turhan, Fatma Karaca; Bas, Bayram (CUKUROVA UNIV, 2021)
Children are affected by messages in novels in terms of gender identity and occupational development, hence this study aims to examine occupational stereotypes. Accordingly, it was designed as a holistic single case study and ninety Turkish children's novels selected by criterion sampling were examined. Document analysis was administered on selected children's novels according to occupational investigation and classification criteria. Data were analysed by using qualitative and quantitative analysis and findings were presented descriptively. Findings revealed that in Turkish children's novels men had various occupations more than women did. Additionally, more detailed information was given about men's occupations. There were occupational areas in which men and women converged and diverged in terms of frequency and variety. Men and women had occupations with both high and low prestige. However, men were more closely associated with occupations with high prestige while women with low prestige. Men and women had both traditional and non-traditional occupations. However, men were mostly associated with traditional occupations and women with non-traditional occupations. Consequently, it was observed that in Turkish children's novels, occupations were processed in line with gender roles. However, counter examples displaying that women were breaking gender roles on occupational grounds and that occupational segregation and stereotypes between men and women was reduced also existed.
Keywords: Children's literature; Turkish children's novels; Occupations; Occupational stereotypes; Gender; PICTURE BOOKS; SEX; REPRESENTATION; ROLES; WOMEN; Education & Educational Research